Implementasi Model Pembelajaran Market Place Activity dalam Meningkatkan Hasil Belajar PAI di SMP Negeri 18 Bandung - Nurlaela, Ilma; Latipah, Siti; Nurhasanah, Siti; Nuralisa, Alis; Maulana, Sultan Aldy; Ridwanudin, Rafi (Permata : Jurnal Pendidikan Agama Islam, 2023)
This study discusses the implementation of the market place activity learning model in improving PAI student learning outcomes at SMP Negeri 18 Bandung. This study aims to describe the market place activity learning model in PAI subjects. This research uses qualitative research with a descriptive approach. Data collection was carried out by interview method with PAI teachers, observation and documentation conducted directly in the field to observe the level of learning activities. This research was conducted at SMP Negeri 18 Bandung in Class VIII in PAI learning. The results of this study explain that the PAI learning design oriented to the 2013 curriculum is of the scientific approach type. The implementation of this learning consists of planning, implementation, and research stages. The supporting factors of this learning model are the principal's leadership, teachers' professionalism, students' activeness and parents' support. While the inhibiting factors are differences in student characteristics, feelings of doubt, shyness, requiring a long time, and students' less relevant catchiness to the material discussed. The advantages of this model can increase students' participation, activeness, independence, learning discipline and have a democratic attitude. The effectiveness of this learning model is well achieved in PAI learning class VIII SMP Negeri 18 Bandung.Keyword: Learning Model; Market Place Activity; PAI Learning Outcomes.